The creation of multimedia electronic books for Thai youth on cultural uniqueness of ASEAN countries - Denduang, Sirintip; Rodhetbhai, Chamnan; Keeratiburana, Ying (Interdisciplinary Research Review, 2016)
This qualitative research was integrated from the thesis, namely: The Innovative Development of an Electronic Book on Cultural Uniqueness of ASEAN Countries for Thai Youth. The purposes of the research were: 1) To study the cultural uniqueness of each ASEAN country, and 2) To create multimedia electronic books for Thai youth. The areas of study were 12educational institutions in Bangkok and its vicinity area. The purposively selected samples were totally 114 informants: 30 experts, 24 practitioners, and 60 Thai youth. The instruments used in the research were surveys, observations, interviews, focus group discussions, and workshops. The research results were a series of 7 multimedia electronic books for Thai youth on the cultural uniqueness of ASEAN countries which were synthesized in accordance with the comments of the experts including the results of the learning needs of the youth. The 7 multimedia electronic books were rhyme named in Thai language: 1) Folkways 2) Food 3) Sheltering 4) Costumes 5) Tourist Places 6) Tradition, and 7) Plays and Performances. Thai youth and public can download them from internet and easily use any leisure facilities available and they are readable both online and offline with devices in every system and platform including computers, tablets, and smartphones.